2004
DOI: 10.1002/jclp.20065
|View full text |Cite
|
Sign up to set email alerts
|

Psychology's dilemma: An institutional neurosis?

Abstract: The term psychology refers both to an institutional discipline and to a subject matter. Henriques, in his article "Psychology Defined" (this issue, pp. 1207-1221), emphasizes the second reference, and its focus can be sharpened by taking into account the first reference. On the one hand, epistemic progress in science is a dynamic process, which, as often as not, cuts across institutional divisions. However, on the other hand there are some problems of disunity that solely concern the institution. That the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Katzko (2004) offers an important call to "elevate the 'process of justification' to the status of a phenomenon for study" through the lens of "an informed curiosity" (p. 1239). In other words, researchers are encouraged to develop methodologies that explore new frontiers in answering the question of how people justify their behavioral investments.…”
Section: Toward a Useful Mass Movementmentioning
confidence: 99%
See 2 more Smart Citations
“…Katzko (2004) offers an important call to "elevate the 'process of justification' to the status of a phenomenon for study" through the lens of "an informed curiosity" (p. 1239). In other words, researchers are encouraged to develop methodologies that explore new frontiers in answering the question of how people justify their behavioral investments.…”
Section: Toward a Useful Mass Movementmentioning
confidence: 99%
“…He argued that my comments regarding the American Psychological Association indicated that I had "confused" problems of the institution with problems of science. Katzko (2004) also emphasized the distinction between the institution of psychology and its subject matter. In a similar vein, Yanchar (2004) saw my proposal as pursing unity per se, which presumably would be about the institution, rather than truth, which would be related to the subject matter.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Despite receiving some critical support for the wide sphere of potential insights it affords (Gilbert, 2004; Haaga, 2004; Katzko, 2004; Shealy, 2005; Stanovich, 2004), the Justification Hypothesis serves as an illustrative example of a recent theory built upon new practical assumptions. Although it is perhaps possible that all of human culture may be best understood as justification systems, constrained and operated by particular psychological mechanisms, counterarguments against such a complete account are already emerging.…”
Section: Justification Hypothesis: a Key To Culturementioning
confidence: 99%
“…Both Katzko (2008) and Shaffer (2008), for instance, argue that several social-phenomena require mind-culture bridgings that exceed the projected theoretical role of the Justification Hypothesis. Others, notably Vazire and Robins (2004), argue that the obvious utility of the Justification Hypothesis may be better understood as the result of several distinct adaptations, each with an alternative set of evolutionary origins to those proposed by Henriques (see also Katzko, 2004; Shealy, 2005; Stanovich, 2004). Regardless of which perspective ultimately triumphs, exploring the Justification Hypothesis as an example exposes the value of tentative practical assumptions that the present authors wish to draw attention to.…”
Section: Justification Hypothesis: a Key To Culturementioning
confidence: 99%